Metabolic reduction of resazurin; location within the cell for cytotoxicity assays. Issue 2 (9th November 2017) - Chen, Jian Lin; Steele, Terry W. J.; Stuckey, David C.
Abstract: Resazurin is widely used as a metabolic indicator for living cells, however, there has been considerable debate in the literature with regards to the specific location in the cell where the non‐fluorescent resazurin is reduced to the strongly fluorescent resorufin. This lack of clarity about the reduction site makes the use of resazurin reduction data in cytotoxicity studies difficult to interpret. In this study, E. faecalis, a Gram‐positive and facultative anaerobic bacterial strain, and the most toxic chlorophenol, pentachlorophenol (PCP), were chosen as models for an anaerobe and toxicant, respectively. By studying the kinetics of resazurin reduction by E. faecalis after different treatments (cell disruption, bacterial filtration, and pre‐exposure to toxicant), we confirmed that resazurin reduction to resorufin by live Gram‐positive and facultative anaerobic bacterial cells can only happen intracellularly under anaerobic conditions, while resorufin reduction to dihydroresorufin can happen both intracellularly and extracellularly. Based on the understanding of these fundamental mechanisms, we suggest that resazurin reduction can be used as a quick bioassay for measuring cytotoxicity. Abstract : Metabolic reduction of resazurin to resorufin by living bacterial cells can only happen intracellularly, while the following reduction of resorufin to dihydroresorufin can happen both intracellularly and extracellularly.